2023
DOI: 10.3390/biomedicines11102735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tiliroside and Lisuride Co-Treatment on the PI3K/Akt Signal Pathway: Modulating Neuroinflammation and Apoptosis in Parkinson’s Disease

Faisal K. Alkholifi,
Sushma Devi,
Mohammed F. Aldawsari
et al.

Abstract: Researchers are actively exploring potential bioactive compounds to enhance the effectiveness of Lisuride (Lis) in treating Parkinson’s disease (PD) over the long term, aiming to mitigate the serious side effects associated with its extended use. A recent study found that combining the dietary flavonoid Tiliroside (Til) with Lis has potential anti-Parkinson’s benefits. The study showed significant improvements in PD symptoms induced by 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) when Til and Lis were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In addition, we found that rTMS was no less effective than L-Dopa.Motor complications secondary to L-Dopa (such as motor uctuations,MF) and L-Dopa-induced dyskinesias (LID) have been a major concern in PD drug therapy.A study of 170 PD patients (117 men, age at onset: 65.1 ± 11.6 years, duration of L-Dopa treatment: 23.8 ± 28.4 months) analyzed the effect of time from onset of PD to initiation of L-Dopa on MF or LID and found that early L-Dopa administration was associated with shorter times from diagnosis to MF (p < 0.001) and LID (p = 0.001).Although disease duration is the most important determinant of motor complications, delaying L-Dopa prolonged the 'complication-free' period [50] .Therefore, for those PD patients who choose to delay treatment with L-Dopa, rTMS for PD dysphagia is a carefully considered option.In addition, an observational study involving 95 PD patients who received L-Dopa-carbidopa intestinal gel (LCIG) to treat dysphagia found that dysphagia signi cantly increased the risk of death and was not related to age, disease duration, dementia, hallucination and other related characteristics.Therefore, dysphagia in PD are a priority in the late stage of PD, even among those receiving LCIG treatment [51] .In late-stage PD patients treated with L-Dopa, higher drug doses may be required to achieve better drug effects, which may lead to more severe motor complications. Therefore, rTMS is an option for such cases.L-Dopa non-response was exhibited in a portion of advanced PD patients with MF and mild to moderate dysphagia, and one study suggested L-Dopa testing as a tool to distinguish these responders from non-responders [52] .Therefore, doctors can consider rTMS in PD patients with no signi cant improvement in swallowing symptoms after L-Dopa testing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that rTMS was no less effective than L-Dopa.Motor complications secondary to L-Dopa (such as motor uctuations,MF) and L-Dopa-induced dyskinesias (LID) have been a major concern in PD drug therapy.A study of 170 PD patients (117 men, age at onset: 65.1 ± 11.6 years, duration of L-Dopa treatment: 23.8 ± 28.4 months) analyzed the effect of time from onset of PD to initiation of L-Dopa on MF or LID and found that early L-Dopa administration was associated with shorter times from diagnosis to MF (p < 0.001) and LID (p = 0.001).Although disease duration is the most important determinant of motor complications, delaying L-Dopa prolonged the 'complication-free' period [50] .Therefore, for those PD patients who choose to delay treatment with L-Dopa, rTMS for PD dysphagia is a carefully considered option.In addition, an observational study involving 95 PD patients who received L-Dopa-carbidopa intestinal gel (LCIG) to treat dysphagia found that dysphagia signi cantly increased the risk of death and was not related to age, disease duration, dementia, hallucination and other related characteristics.Therefore, dysphagia in PD are a priority in the late stage of PD, even among those receiving LCIG treatment [51] .In late-stage PD patients treated with L-Dopa, higher drug doses may be required to achieve better drug effects, which may lead to more severe motor complications. Therefore, rTMS is an option for such cases.L-Dopa non-response was exhibited in a portion of advanced PD patients with MF and mild to moderate dysphagia, and one study suggested L-Dopa testing as a tool to distinguish these responders from non-responders [52] .Therefore, doctors can consider rTMS in PD patients with no signi cant improvement in swallowing symptoms after L-Dopa testing.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated a significant presence of apoptotic neurons in the midbrain of individuals with PD. The progression of PD involves causative factors triggering the apoptosis of otherwise healthy neurons [ 9 ]. Consequently, apoptotic signaling exacerbates the risk of additional pathological events, including neuro-inflammation, contributing to further damage to neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in Alzheimer-like mice, linalool reduced neurotoxicity and improved cognitive function by activating Nrf2/HO-1 and BDNF [27,37]. 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) is identified as a standard model of PD for its ability to induce numerous hallmarks of PD, including apoptosis, inflammation, energy failure, and oxidative stress in many mammals such as monkey and mice [9,[38][39][40][41]. MPTP can pass into the BBB owing to its high lipophilicity and quickly transforms to its active metabolite 1-methyl-4-phenylpyridinium ion (MPP + ) by monoamine oxidase B in glial cells, which then causes impairment to the nigrostriatal dopamine pathway and causes dopaminergic neuron damage [42,43].…”
Section: Introductionmentioning
confidence: 99%